Synthetic, Structural and Thermal Studies of Some Coordination Polymers of Sebacyl Bis-Biuret with First Transition Series Metals - M. Roy, Sushmita; Juneja, H.D.; Munshi, K.N. (Asian Journal of Chemistry, 2010)
Some new polymeric chelates have been synthesized by combining sebacyl bis-biuret with metals of first transition series, viz., Mn(II), Co(II), Ni(II), Cu(II) and Zn(II). These were characterized with the help of elemental analysis, infrared and reflectance spectral and magnetic studies. A detailed thermal study was carried out and thermal stability compared. Freeman-Carrol and Sharp-Wentworth methods have been used to calculate the activation energy and order of reaction. Thermodynamic parameters have been calculated, using the data of Freeman-Carrol method. The results obtained have been suitably discussed.